Learning from addiction: Craving of prescription opioids in chronic pain sufferers. (November 2022) - Strigo, Irina A.; Murphy, Emily; Mitchell, Jennifer M.; Spadoni, Andrea D.
Abstract: Prescription opioids are a primary driver of opioid-related deaths. Although craving is a substantial component of OUD, the degree to which craving leads to misuse among chronic pain patients on long-term prescription opioids is unknown. A clear understanding of the factors that lead to misuse in this vulnerable population is needed for the development of safe and effective practices for opioid taper. This narrative review summarizes the relevant literature on the role of craving in addiction and chronic pain through epidemiological and behavioral studies. The first part of this review examines the role of craving in predicting opioid use/misuse in individuals with chronic pain with and without OUD. The second part covers methods on how craving is evaluated experimentally using both subjective and objective measures and provides related findings. The overall goal of this review is to facilitate the development of a population-specific description of craving in those who use opioids to control chronic pain and to describe how it may be mechanistically linked to patterns of opioid (mis)use. Highlights: The concept of craving is complex, subjective, with heterogeneous etiologies. The degree to which craving plays a role in opioid consumption in chronic pain is poorly understood. Severity of psychiatric symptoms are associated with higher craving and greater opioid (mis)use among chronic pain patients. There is little evidence that pain severity reinforces opioid craving and (mis)use in chronic pain. Currently available measures to assess craving may translate poorly to chronic pain patients.